Transforming the workforce for children birth through age 8 : a unifying foundation - Allen, LaRue, 1950-; Kelly, Bridget Burke, 1973- (The National Academies Press, 2015)
"Children are already learning at birth, and they develop and learn at a rapid pace in their early years. This provides a critical foundation for lifelong progress, and the adults who provide for the care and education of young children bear a great responsibility for these children's health, development, and learning. The Institute of Medicine (IOM) and National Research Council (NRC) were commissioned to explore the implications of the science of child development for the professionals who work with children birth through age 8. In the resulting report, Transforming the workforce for children birth through age 8: a unifying foundation, the committee finds that much is known about what professionals who provide care and education for children need to know and be able to do and what professional learning supports they need. However, that knowledge is not fully reflected in the current capacities and practices of the workforce, the settings in which they work, the policies and infrastructure that set qualifications and provide professional learning, and the government and other funders who support and oversee these systems. The report offers recommendations to build a workforce that is unified by the foundation of the science of child development and early learning and the shared knowledge and competencies that are needed to provide consistent, high-quality support for the development and early learning of children from birth through age 8"--Publisher's website